Pengaruh Penggunaan Modul Berbasis Research pada Pembelajaran Think Pair Share dan Group Investigation terhadap Pemahaman Konsep dan Kemampuan Metakognisi Peserta Didik Kelas X SMA Negeri 1 Boyolali Tahun Ajaran 2013/2014 - ARIEF RIDHO WICAKSONO; Sri Widoretno; Nurmiyati Nurmiyati (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2015)
The purpose of the research to determine effect of the use of Module-Based Research on Learning Model of Think Pair Share and Group Investigation to Understanding of Concept and Metacognition Ability of 10th Grade Students at SMA Negeri 1 Boyolali 2013/2014 Academic Year. This research was quasi experiment research which use Pretest-postest Nonequivalent control group design. The research population was all students of 10th Grade at SMA Negeri 1 Boyolali 2013/2014 Academic Year. The sample is taken by using Cluster Random Sampling method, in order to obtain 4 class experimental and 1 control class with the same capabilities. Experimental class is a class with treatment of different learning, namely TPS + module-based research, GI + module-based research, TPS, GI, and one class as a control. Data was collected using a multiple-choice test, test description, and observation sheets. Hypothesis testing using Anacova test. The research concluded that there are significant differences to understanding concept of students as a result of the use Think Pair Share and Group Investigation with module-based research. Results for metacognition abilities showed no significant difference from the treatment that used, namely TPS + module-based research, GI + module-based research, TPS, GI towards metacognitive abilities of of 10th Grade Students at SMA Negeri 1 Boyolali 2013/2014 Academic Year.